2016
DOI: 10.35188/unu-wider/2016/168-0
|View full text |Cite
|
Sign up to set email alerts
|

Unintended consequences of economic sanctions for human rights: Conflict minerals and infant mortality in the Democratic Republic of the Congo

Abstract: provides economic analysis and policy advice with the aim of promoting sustainable and equitable development. The Institute began operations in 1985 in Helsinki, Finland, as the first research and training centre of the United Nations University. Today it is a unique blend of think tank, research institute, and UN agency-providing a range of services from policy advice to governments as well as freely available original research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…33 Qualitative evidence suggests that people in mining communities could no longer afford to visit healthcare facilities or pay for their children's schooling; moreover, the economic effects where felt throughout the eastern provinces as artisanal miners could no longer afford to pay for goods, services and agricultural products (Cuvelier et al 2014;Wimmer and Hilgert 2011). Using quantitative data, Parker et al (2016) further find that the probability of infant deaths increased by at least 143% in villages near artisanal mines targeted by the Dodd-Frank act.…”
Section: Appendix 2: Dodd-frankmentioning
confidence: 95%
“…33 Qualitative evidence suggests that people in mining communities could no longer afford to visit healthcare facilities or pay for their children's schooling; moreover, the economic effects where felt throughout the eastern provinces as artisanal miners could no longer afford to pay for goods, services and agricultural products (Cuvelier et al 2014;Wimmer and Hilgert 2011). Using quantitative data, Parker et al (2016) further find that the probability of infant deaths increased by at least 143% in villages near artisanal mines targeted by the Dodd-Frank act.…”
Section: Appendix 2: Dodd-frankmentioning
confidence: 95%
“…Most articles identifying physical effects (59%; 16/27) provided evidence for increased mortality—a large majority from within those articles (88%; 14/16) for infant mortality, 5,4153 a quarter (25%; 4/16) for maternal mortality, 42,47,48,52,53 and more than a third (36%; 6/16) for general mortality. 48,49,52,54,55 Reasons reported for increased mortality, especially infant and maternal mortality, included mortality from infectious disease, 5,41,45,51,54 noncommunicable diseases, 41,48 nutrition-related causes, 5,41,42,4648,51 increased poverty, 42,45,46,49 reduced access to medicines and health care, 41,42,4447,49,51 and destruction of public infrastructure. 41,42,45 Two articles (13%; 2/16) reported that compared to war or natural emergencies, the highest rates of infant mortality occurred under sanctions, concluding that prolonged sanctions are more lethal for infants and children than other sources of social and political distress.…”
Section: Direct Impact Of Sanctions On Healthmentioning
confidence: 99%
“…A large majority of the articles (70%; 26/37) that reported on the economic effects of sanctions described that during the sanctions period, there were decreases in income levels, 44,47,48,50,52,54,65,71,75 increases in individual and household poverty, 41,47,48,50,52,54,65,76 and increases in unemployment due to bankruptcy of domestic industries. 13,39,40,42,47,48,59,60,67 A small minority (12%; 3/26) reported that women in particular experienced increasing economic burdens, 42,49,60 such as unemployment, 42,49,60 sex work to survive, 60 disruptions in child rearing and feeding, 42 and breakdown of family structures. 42 Declining incomes, in combination with sanctions-inflicted inflation, exhausted household resources and limited choices for survival 44,48,50,53,66,67 ; reduced migration opportunities even as the imperative to migrate was itself exacerbated by sanctions 46 ; and increased expenditures on food, 14,42,49,65,66,71 housing, 48,53 electricity, 48 and children's education.…”
Section: Indirect Impact Of Sanctions On Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this decision, the Malaysia Smelting Corporation (MSC), which previously purchased up to 80% of eastern Congolese tin, stopped sourcing minerals from the DRC.34 Qualitative evidence suggests that people in mining communities could no longer afford to visit healthcare facilities or pay for their children's schooling; moreover, the economic effects where felt throughout the eastern provinces as artisanal miners could no longer afford to pay for goods, services and agricultural products(Cuvelier et al 2014;Wimmer and Hilgert 2011). Using quantitative data,Parker et al (2016) further find that the probability of infant deaths increased by at least 143% in villages near artisanal mines targeted by the Dodd-Frank act.…”
mentioning
confidence: 95%